Compromised endothelial progenitor cell exosomal communication with endothelial cells in hypertension ischemia conditions - Chen, Shuzhen; Polaki, Venkata; Bihl, Ji C.; Wang, Jinju (Frontiers in Stroke, 2022)
We have previously demonstrated that EPC-exosomes (EPC-EXs) can protect endothelial cells (ECs) against hypoxia injury. Given EX function vary upon cellular status and EPC function is declined in hypertension, we speculate the function of EPC-EXs is altered in hypertension-ischemia conditions. Here, we studied the EPC-EX mediated communications of EPCs with ECs in hypertension-ischemia conditions. EPC-EXs were prepared from the bone marrow EPCs of wild type (WT) and hypertensive renin transgene (R+) mice (WT-EPC-EXs and R-EPC-EXs, respectively). To mimic hypertension-ischemia injury, ECs were treated with angiotensin II (Ang II; 10-6 M) plus hypoxia (1% O2 for 6 hrs) and reoxygenation (21% O2 for 24 hrs). To determine the function of EPC-EXs, ECs were co-cultured with EXs during the reoxygenation period. EX uptake efficiency, EC viability and angiogenic function were assessed. Our results showed that: 1) The incorporation efficiency of R-EPC-EXs by ECs were significantly decreased as compared to the WT-EPC-EXs. 2) Ang II plus hypoxia reoxygenation-injured ECs displayed decreased cell viability, increased cell apoptosis and compromised angiogenic ability, which were alleviated by R-EPC-EXs. 3) WT-EPC-EXs elicited better effects than R-EPC-EXs did on protecting ECs against hypertension plus hypoxia injury. In conclusion, our data have demonstrated that EPC-EXs mediated communication of EPCs and ECs is compromised in hypertension-ischemia condition, suggesting that impairment of EPC exosomal communication might contribute to the exaggerated cerebral ischemia injury in hypertension-associated ischemic stroke.